Pemberian Sanksi dan Efek Jera Pemberian Sanksi dan Efek Jera terhadap Negara yang Melanggar Hukum Humaniter Internasional - Nasution, Muhammad Mukmin Toat (Fakultas Ilmu Sosial dan Ilmu Politik - Universitas Garut, 2025)
The provision of sanctions against countries that violate international humanitarian law is one of the mechanisms to enforce international norms. This sanction aims to create a deterrent effect, so that the country concerned does not repeat the violation. This study analyzes the various types of sanctions applied by the international community and their effectiveness in providing a deterrent effect. The methodology used is literature study and case analysis. The results of the study show that although sanctions can have a deterrent effect, their success is highly dependent on the political and economic context of the sanctioned country.